Managing the entanglement: complexity leadership in public sector systems - Murphy, Joanne; Rhodes, Mary Lee; Meek, Jack W.; Denyer, David (Wiley, 2016)
Complexity in public sector systems requires leaders to balance the administrative practices necessary to be aligned and efficient in the management of routine challenges and the adaptive practices required to respond to dynamic circumstances. Conventional notions of leadership in the field of public administration do not fully explain the role of leadership in balancing the entanglement of formal, top-down, administrative functions and informal, emergent, adaptive functions within public sector settings with different levels of complexity. Drawing on and extending existing complexity leadership constructs, this article explores how leadership is enacted over the duration of six urban regeneration projects representing high, medium, and low levels of project complexity. The article suggests that greater attention needs to be paid to the tensions inherent in enabling leadership if actors are to cope with the complex, collaborative, cross-boundary, adaptive work in which they are increasingly engaged